FAKTOR MEMPENGARUHI KEPUTUSAN NASABAH PADA TABUNGAN MUDHARABAH BANK UMUM SYARIAH PERIODE 2015-2019 DI INDONESIA - Maryati, Mari; Purnomo, Hadi; Sutisnawati, Yayah; Herlina, Maya (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2022)
The purpose of this research is to understand the effect of inflation and financing to deposit ratio on Mudhrabah Savings in Islamic commercial banks in Indonesia in the period 2015-2019. Financial statements for the period 2015-2019 with the number of 6 Islamic banking companies were sampled in this research. Data processing results are obtained using multiple regression analysis. The results of the T test showed that inflation and FDR had a significant positive influence on mudharabah savings, while the results of the F test showed that inflation, and financing to deposit ratio had a significant effect on mudharabah savings.